Sistem Penjualan Obat Menggunakan Metode Regresi Linear Berganda Di Apotek Cahaya Farma - Iqbal Rahmat Adha; Khairil Khairil; Eko Suryana (UNIVED Press, 2026)
This research aims to develop a web-based drug sales system at Cahaya Farma Pharmacy, equipped with a drug inventory prediction feature to assist the pharmacy in more efficient stock management. The system was developed using the PHP programming language with MySQL database support for data storage, and employs the Multiple Linear Regression method as an analytical tool to estimate future drug inventory needs. Test results showed the method was effective in predicting drug inventory levels. In the January 2025 test, the prediction for Amoxicillin 500mg Tablets yielded 32 results compared to the actual data of 40, with an accuracy rate of 80% (Good category). Meanwhile, the prediction for Paracetamol Tablets yielded 22 results from the actual data of 27, with an accuracy rate of 81.48% (Good category). These results demonstrate that the Multiple Linear Regression method is capable of representing the relationship between sales, purchases, and inventory variables with a good level of accuracy, thus providing a basis for decision-making regarding drug stock management at Cahaya Farma Pharmacy